CircRNAs: Roles in regulating head and neck squamous cell carcinoma - Han, Xiao; Tian, Ruxian; Wang, Cai; Li, Yumei; Song, Xicheng (Frontiers in Oncology, 2022)
Head and neck squamous cell carcinoma (HNSCC), the most common head and neck malignant tumor, with only monotherapy, is characterized by poor prognosis, and low 5-year survival rate. Due to the lack of therapeutic targets, the targeted drugs for HNSCC are rare. Therefore, exploring the regulation mechanism of HNSCC and identifying effective therapeutic targets will be beneficial to its treatment of. Circular RNA (CircRNA) is a class of RNA molecules with a circular structure, which is widely expressed in human body. CircRNAs regulate gene expression by exerting the function as a miRNA sponge, thereby mediating the occurrence and development of HNSCC cell proliferation, apoptosis, migration, invasion, and other processes. In addition, circRNAs are also involved in the regulation of tumor sensitivity to chemical drugs and other biological functions. In this review, we systematically listed the functions of circRNAs and explored the regulatory mechanisms of circRNAs in HNSCC from the aspects of tumor growth, cell death, angiogenesis, tumor invasion and metastasis, tumor stem cell regulation, tumor drug resistance, immune escape, and tumor microenvironment. It will assist us in discovering new diagnostic markers and therapeutic targets, while encourage new ideas for the diagnosis and treatment of HNSCC.